1992
DOI: 10.1007/bf02636061
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative action of Maillard reaction volatiles: Influence of Maillard solution browning level

Abstract: Maillard reaction volatile compounds were prepared by heating a glucose-glycine solution. The antioxidant effect of the volatiles was tested in soybean oil (SBO) thermoxidation. Volatile compounds were transferred from the heated Maillard solution to the oil with a gas-tight syringe after removing the same volume of oil headspace (air). Standard accelerated oxidation was performed by heating the SBO at 90°C. Antioxidant activity was evaluated through peroxide value and headspace gas chromatographic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…These compounds were found to break the radical chain by donation of a hydrogen (8,9). These results were also confirmed by Elizalde et al (10,11), Severini and Lerici (12) and Munari et al (13). Further experimental evidence showed that MRPs are effective as metal chelating agents and that they can reduce hydroperoxide to nonradical products (8,(14)(15)(16).…”
Section: Introductionsupporting
confidence: 89%
“…These compounds were found to break the radical chain by donation of a hydrogen (8,9). These results were also confirmed by Elizalde et al (10,11), Severini and Lerici (12) and Munari et al (13). Further experimental evidence showed that MRPs are effective as metal chelating agents and that they can reduce hydroperoxide to nonradical products (8,(14)(15)(16).…”
Section: Introductionsupporting
confidence: 89%
“…Seed roasting before oil extraction gives it a characteristic good flavor and is reported to improve the stability of some oils such as sesame [2] and safflower [3], partly due to certain reactions such as the Maillard reaction occurring during roasting. Maillard reaction products were reported to lengthen the induction period of oil oxidation and decrease the rate of oxidation at the propagation step [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Later they suggested that some of these volatile compounds were mainly responsible for the antioxidant activity exhibited by a dichloromethane extract of coffee brew (Yanagimoto, Ochi, Lee, & Shibamoto, 2004). Furthermore, typical volatile compounds formed in Maillard reaction model systems have been reported to inhibit oxidation of lipids (Elizalde, Bressa, & Rosa, 1992;Osada & Shibamoto, 2006). Also, other authors observed that certain volatile compounds produced in the roasting process of almonds displayed an antioxidant effect (Severini, Gomes, De Pilli, Romani, & Massini, 2000).…”
Section: Introductionmentioning
confidence: 99%